A framework for adoption and implementation of green IT/IS practice in IT governance - Anthony Jnr, Bokolo; Che Pa, Noraini (Society of Digital Information and Wireless Communications (SDIWC), 2015)
Green information technologies and systems IT/IS are initiatives, strategies and programs that directly or indirectly address environmental sustainability in organizations. While practitioners have begun to focus on Green IT/IS, however there is few research in this area. The aim of this paper is to develop a framework to assist practitioners and organisations in the adoption of green IT/IS practices in IT Governance. Existing green IT/IS literature were reviewed. Hence the paper concern research that addresses Green IT, Green IS and environmental sustainability mainly in domain of information technology governance (IT Governance). Findings from this paper show the components and attributes that are to be considered in implementing Green IT/IS in IT Governance. Thus the framework can also be used as a guide for future research in this domain.